PEMBINAAN BATIK PONOROGO - Sri Wuryani (Abdi Seni, 2016)
PKM activity is one of University Three Services (Tri Darma Perguruan Tinggi) that lecturer has todo. PKM is an activity conducted by lecturer as university interest toward society. This activity expected has direct effect for people. For this reason, it is adjusted with people needs. The assistance for batik Ponorogo is activity conducted by lecturer from Indonesian Art Institute of Surakarta (ISI Surakarta) at High School 1 Ponorogo (SMAN 1 Ponorogo). ISI Surakarta chooses this place as its interest toward batik especially Ponorogo and it represented by assist young generation to carry oncultural heritage. The headmaster and officials accept this activity with planning batik uniform fortheir students, of course, batik creation by them selves. Batik training aimed to give necessary skill like design skill and make handmade batik. After training, students are expected can make handmade batik fabric, make batik design and batik creation as the beginning step to realize batik uniform of SMAN 1 Ponorogo East Java. Expectation of PKM activity is students motivated to have creationin batik motif and then new motif of batik will emerge at Ponorogo (especially) and this nation (generally).Key words : batik, Ponorogo, uniform.